2021
DOI: 10.3389/fphar.2021.645858
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Extracellular Matrix Interactions With Human Lung Basal Stem Cells in Lung Development, Disease, and Airway Modeling

Abstract: The extracellular matrix (ECM) is not simply a quiescent scaffold. This three-dimensional network of extracellular macromolecules provides structural, mechanical, and biochemical support for the cells of the lung. Throughout life, the ECM forms a critical component of the pulmonary stem cell niche. Basal cells (BCs), the primary stem cells of the airways capable of differentiating to all luminal cell types, reside in close proximity to the basolateral ECM. Studying BC-ECM interactions is important for the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 173 publications
(391 reference statements)
0
11
0
1
Order By: Relevance
“…Indeed, upon damage, the neighboring epithelial cells will undergo phenotypic changes, due to loss of contact inhibition from neighboring cells and an increasing gradient of factors (e.g., cytokines and growth factors) from the wound site, which enable them to migrate over and seal the wound ( 47 ). Gene expression analysis of those spreading cells in human showed that these cells were positive for vimentin and KRT14, illustrating the important role of basal cells in the initial phase after injury ( 48 , 49 ). Interestingly, secretory epithelial cells (i.e., goblet and club cells) have the capacity to dedifferentiate in absence of basal cells and become functional TP63 + and KRT5 + airway progenitor cells ( 49 51 ).…”
Section: Sensing Tissue Damage and Orchestrating Epithelial Repair Af...mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, upon damage, the neighboring epithelial cells will undergo phenotypic changes, due to loss of contact inhibition from neighboring cells and an increasing gradient of factors (e.g., cytokines and growth factors) from the wound site, which enable them to migrate over and seal the wound ( 47 ). Gene expression analysis of those spreading cells in human showed that these cells were positive for vimentin and KRT14, illustrating the important role of basal cells in the initial phase after injury ( 48 , 49 ). Interestingly, secretory epithelial cells (i.e., goblet and club cells) have the capacity to dedifferentiate in absence of basal cells and become functional TP63 + and KRT5 + airway progenitor cells ( 49 51 ).…”
Section: Sensing Tissue Damage and Orchestrating Epithelial Repair Af...mentioning
confidence: 99%
“…The degradation is primarily performed by matrix metalloproteinases (i.e., MMP-3, MMP-9, and MMP-11), that are mainly released by the migratory basal cells ( 28 , 37 ). In addition, those migratory basal cells also deposit new ECM compounds that ease their migration and provide a temporary provisional barrier that covers the wound in attendance of full resolution, a mechanism that is again proposed to be initiated by TGF-β ( 48 , 65 ). While colonizing the denuded epithelium, the migratory progenitor cells start to proliferate to completely cover the damaged site.…”
Section: Sensing Tissue Damage and Orchestrating Epithelial Repair Af...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is immediately obvious that the ECM provides an elaborate framework that maintains structural integrity during lung organogenesis. However, it also plays a critical role in defining stem cell fate and maturation of the lung [ 20 , 110 ]. The pulmonary ECM is a nexus of biochemical and mechanical cues that instructs stem cell behavior during lung development and regeneration [ 111 ].…”
Section: Engineering Cell–matrix Interactions To Optimize the In Vitr...mentioning
confidence: 99%
“…Two different technologies have recently gained popularity for creating physiomimetic models to recreate the ECM ( Busch, Lorenzana, and Ryan 2021 ) and the mechanobiological signals in vitro : 3D cell cultures ( Habanjar et al, 2021 ) and organ-on-a-chip devices ( Mertz, Ahmed, and Takayama 2018 ; Benam, Burgess, and Stewart 2021 ). Indeed, it has been shown that lung ECM can be obtained by decellularizing the native tissues with detergents and enzymes ( Nonaka et al, 2014 ) and then pulverized and reconstituted in the form of hydrogels suitable for 3D cell culture ( Pati and Cho 2017 ).…”
Section: Introductionmentioning
confidence: 99%